Long-Term Warming of Baltic Sea Coastal Waters Affects Bacterial Communities in Bottom Water and Sediments Differently - Seidel, Laura; Broman, Elias; Ståhle, Magnus; Nilsson, Emelie; Turner, Stephanie; Hendrycks, Wouter; Sachpazidou, Varvara; Forsman, Anders; Hylander, Samuel; Dopson, Mark (Frontiers in Microbiology, 2022)
Coastal marine ecosystems are some of the most diverse natural habitats whilst being highly vulnerable in the face of climate change. The combination of anthropogenic influence from land and ongoing climate change will likely have severe effects on the environment, but the precise response remains uncertain. This study compared an unaffected ‘control’ Baltic Sea bay to a ‘heated’ bay that has undergone artificial warming from cooling water release from a nuclear power plant for approximately 50 years. This heated the water in a similar degree to IPCC SSP5-8.5 predictions by 2100 as natural systems to study temperature related climate change effects. Bottom water and surface sediment bacterial communities and their biogeochemical processes were investigated to test how future coastal water warming alters microbial communities, shifts seasonal patterns such as increased algae blooming, and influences nutrient and energy cycling including elevated respiration rates. 16S rRNA gene amplicon sequencing and geochemical parameters demonstrated that heated bay bottom water bacterial communities were influenced by increased average temperatures across changing seasons resulting in an overall Shannon´s H diversity loss and shifts in relative abundances. In contrast, the Shannon´s diversity increased in the heated surface sediments. The results also suggested a trend towards smaller sized microorganisms within the heated bay bottom waters, with a 30 % increased relative abundance of small size picocyanobacteria in the summer (June). Furthermore, bacterial communities in the heated bay surface sediment displayed little seasonal variability, but did show potential changes of long-term increased average temperature in the interplay with related effects on bottom waters. Finally, heated bay metabolic gene predictions from the 16S rRNA gene sequences suggested raised anaerobic processes closer to the sediment-water interface. In conclusion, climate change will likely alter microbial seasonality and diversity leading to prolonged and increased algae blooming and elevated respiration rates within coastal waters.